UPAYA PEREMPUAN SINGLE PARENT PADA SEKTOR INFORMAL DALAM PEMENUHAN KEBUTUHAN KELUARGA - Simanullang, Lusi Marlina; Elvawati, Elvawati; Isnaini, Isnaini (Universitas Tanjungpura, 2022)
This research is motivated by the high number of single-parent women, 40% of whom work in the informal sector, and the income and expenses of single-parent women are not balanced, thus making women constrained in meeting family needs. This study aims to describe and analyze the efforts of single-parent women in the informal sector in meeting family needs in Nagari Tanjung Beringin, Lubuk Attitude District, and Pasaman Regency. The approach used in this study is a descriptive qualitative approach. Observation, interviews, and documentation studies carried out data collection techniques. The unit of analysis in this study is the individual. The Miles and Huberman model uses the data analysis technique, namely data collection, data reduction, data presentation, and concluding. The conclusion from the results of this study is that single-parent women who work in the informal sector to meet the needs of their families make efforts to meet the requirements; namely, single-parent women have side jobs. In contrast, they use family relationships, collect agricultural products such as vegetables, chocolate, corn, and areca nut, borrow funds from formal and non-formal financial institutions, and other single-parent women make savings to meet their needs families.